Sustainability practices in the aviation sector: a study of UAE-based airlines. (2017) - Alameeri, Amal; Ajmal, Mian M.; Hussain, Matloub; Helo, Petri T.
This study aims to develop a framework for identification, categorisation, and prioritisation of sustainability practices in airlines. After extensive literature review to identify the main criteria and sub-criteria of sustainability practices, analytical hierarchical process (AHP) is utilised to prioritise them. Study has identified eight main criteria and 33 sub-criteria of sustainability practices relevant to airlines. It is found that government management equally with innovation management has the top priority in the United Arab Emirates (UAE) based airlines under sustainability practices. Similarly, the three most important sustainability sub-criteria in these airlines are to obey policy requirement, marketing innovation and innovation and development. Results are derived from two UAE-based national airlines, therefore these cannot be generalised to other airlines. Future research is needed in all airlines of UAE to get the whole picture of sustainability practices. The developed sustainability framework provides a good understanding for the most important sustainability practices the airlines should focus on. Also, the present areas that need to increase effort and focus are the social and environmental practices by the airlines.